2020
DOI: 10.1192/bja.2020.64
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurring mental disorder and substance use disorder in young people: aetiology, assessment and treatment

Abstract: SUMMARY Dual diagnosis is one of several terms used to identify individuals diagnosed with a co-occurring mental disorder and substance use disorder. The existence of a dual diagnosis in adolescents is often associated with functional impairment in various life domains, causing physical health problems, relational conflicts, educational/vocational underachievement and legal problems. Dual diagnosis is difficult to treat and can result in tremendous economic burden on healthcare, education and justice system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Merikangas et al [ 18 ] reported rates of co-occurring mental health disorders as high as 77% among a community sample of youth with a SUD diagnosis. Regardless of precedence, both mental health and SUD can have exacerbating effects on each other if not treated, highlighting the importance of early diagnosis and early access to care [ 19 ]. However, current practices utilizing an integrative approach to diagnose and treat SUD and concurrent mental health disorders have yet to be widely implemented [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Merikangas et al [ 18 ] reported rates of co-occurring mental health disorders as high as 77% among a community sample of youth with a SUD diagnosis. Regardless of precedence, both mental health and SUD can have exacerbating effects on each other if not treated, highlighting the importance of early diagnosis and early access to care [ 19 ]. However, current practices utilizing an integrative approach to diagnose and treat SUD and concurrent mental health disorders have yet to be widely implemented [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research studies have confirmed the efficacy of brief interventions in assisting youngsters to reduce their alcohol consumption and beautifying their standard health and well-being [ 7 , 8 , 9 , 10 ]. Nevertheless, it is vital to understand that the effectiveness of these short interventions can range primarily based on numerous elements, consisting of an individual’s motivation to change, the severity of their substance use, and the presence of any occurring mental health disorders [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst SUDs prevalence have increased across the world, existing evidence shows that over 80 to 85% of people with mental disorders in LMICs do not have access to appropriate mental healthcare especially the out of reach populations [ 5 ]. Arguably, there is an overlap between people who require treatment for SUDs and other mental disorders [ 9 ]. Nevertheless, the worsening problems of SUDs continue to compound the existing unmet mental health needs [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arguably, there is an overlap between people who require treatment for SUDs and other mental disorders [ 9 ]. Nevertheless, the worsening problems of SUDs continue to compound the existing unmet mental health needs [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%